For this case we have to by definition, if two lines are parallel then their slopes are equal.
We find the slope of the line AB:
[tex](x1, y1): (- 3,0)\\(x2, y2): (- 6,5)[/tex]
[tex]m = \frac {y2-y1} {x2-x1} = \frac {5-0} {- 6 - (- 3)} = \frac {5} {- 6 + 3} = \frac {5} { -3} = - \frac {5} {3}[/tex]
Thus, the parallel line is of the form:
[tex]y = - \frac {5} {3} x + b[/tex]
If the line passes through the origin, then we have the point (0,0):
[tex]0 = - \frac {5} {3} (0) + b\\b = 0[/tex]
Then, the equation is:
[tex]y = - \frac {5} {3} x\\3y = -5x\\3y + 5x = 0[/tex]
Answer:
OPTION C